Analisis Prosedur Audit Pengujian Substantif Kas dan Setara Kas BPR THV Oleh Kap Joen dan Rekan - Femmylia Ferdyan Putri; Diah Hari Suryaningrum (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Current asset accounts at rural banks, which are very liquid and easy to move, are in the form of cash and cash equivalents. In rural banks, cash equivalents are in the form of placements with other banks. This account plays an important role in operational activities because it is a place to store company funds for business operations. The company carries out financial audits to determine the cash balance and cash equivalents that have been presented fairly. Examination of cash and cash equivalents accounts through several procedures, one of which is substantive testing. Substantive testing consists of bank confirmation, journal tracing, ledger verification, reconciliation, and presentation and partition evaluation. This research aims to determine whether the audit procedures for substantive testing of cash and cash equivalent accounts carried out by KAP Joen and Rekan for the BPR THV audit are the same as audit procedures in general for substantive testing of cash and cash equivalent accounts. This research method uses qualitative and descriptive analysis techniques. This research concluded that the audit procedures for substantive testing of BPR THV cash and cash equivalents accounts carried out by KAP Joen and Rekan were the same as general audit procedures for substantive testing of cash and cash equivalents accounts. However, the smoothness of substantive audit testing depends on documents from the client; the unpreparedness of documents as audit evidence hinders the audit process.